Сказ в жанровых песнях Александра Галича - Bartosz Osiewicz (Studia Rossica Posnaniensia)
This article is devoted to an analysis of genre songs by Alexander Galich. Thanks to the epic element presented in these songs, the poet uses skaz to create a portrait of a contemporary epoch. By introducing skaz, which is a method of narration imitating the oral utterance, the author strictly refers to the literary tradition of Gogol, Babel and Zoshchenko. The main role of Galich’s skaz is irony, which can be perceived only by a prepared reader, whom the poet is counting on.